2013
DOI: 10.1242/jeb.092031
|View full text |Cite
|
Sign up to set email alerts
|

RNA interference of glycerol biosynthesis suppresses rapid cold hardening of the beet armyworm,Spodoptera exigua

Abstract: SUMMARYThe beet armyworm, Spodoptera exigua, is a freeze-susceptible species that overwinters in temperate zones without diapause. A rapid cold hardening (RCH) and supercooling capacity usually play crucial roles in survival during the overwintering period. This study identified a cryoprotectant as a RCH factor of S. exigua. Pre-exposure of S. exigua larvae to 4°C significantly increased survival at −10°C in all developmental stages from egg to adult. RCH was dependent on the duration of the pre-exposure perio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
41
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 39 publications
(44 citation statements)
references
References 42 publications
3
41
0
Order By: Relevance
“…Sugars are primarily used for the metabolic Control (feeding) Starvation production of ATP energy and carbon source. Compared to glucose as the main blood sugar, trehalose is the principal hemolymph sugar in insects including S. exigua [41,54]. Our current study showed a fluctuation of trehalose levels in the hemolymph of S. exigua larvae in a diel rhythm according to feeding behavior.…”
Section: Discussionsupporting
confidence: 46%
See 1 more Smart Citation
“…Sugars are primarily used for the metabolic Control (feeding) Starvation production of ATP energy and carbon source. Compared to glucose as the main blood sugar, trehalose is the principal hemolymph sugar in insects including S. exigua [41,54]. Our current study showed a fluctuation of trehalose levels in the hemolymph of S. exigua larvae in a diel rhythm according to feeding behavior.…”
Section: Discussionsupporting
confidence: 46%
“…Especially, its massive feeding activity during last instar allows the larvae to grow more than four times in body weight and gives serious economic damage to crops [30]. Its major sugar in hemolymph (= insect blood) is trehalose [41]. Like other insects to keep a constant level of hemolymph trehalose, S. exigua needs to control the fluctuating trehalose levels along with nutrient uptake from the gut to the hemolymph under a circadian feeding rhythm.…”
Section: Introductionmentioning
confidence: 99%
“…Several genes of S . exigua are modulated in their expressions by their specific dsRNA treatments and exhibit significant RNAi efficacies [ 19 24 ]. Moreover, oral feeding of dsRNA was effective to induce significant RNAi in S .…”
Section: Introductionmentioning
confidence: 99%
“…지방체는 척추동물의 간과 비 슷한 역할을 하며, 대사중심으로써 trehalose-6-phosphate synthase를 이용하여 trehalose를 생산한다 (Kern et al, 2012). 파밤나방에서 보고된 것처럼 (Park and Kim, 2013) * The expression level of each contig can be divided into upregulation (log 2 Fc>2), downregulation (log 2 Fc<-2), and not meaningful (-2<log 2 Fc<2), compared to the control. 2<log 2 Fc<10: ▲; 10<log 2 Fc<50: ▲▲; -10<log 2 Fc<-2: ▼; -50<log 2 Fc<-10: ▼▼ Note…”
Section: 배추좀나방 사육mentioning
confidence: 99%